Assessment of exercise performance and aerobic efficiency by the results of veloergometry in girls aged 11-14 years with the weak sight. - V. V. Maryukhnich; V. V. Klapchuk (Medičnì Perspektivi)
Secondary school age is a critical period in the development of a person. For the purpose to evaluate and compare the level of exercise performanceand aerobic performance in 90 girls at the age of 11-14 with impaired vision in the form of weak and moderate myopia, as well as myopic astigmatism, veloergometric test PWC170 was used. Power of performed load was estimated and indices of maximum oxygen consumption were calculated. It is established that absolute levels of physical performance and maximal oxygen consumption in girls significantly increased with age: 8.7%, 17,9% and 19% test PWC170 and 8.4%, 6.4% and 13.4%– aerobic performance by GMT. Relatively to body mass they decreased by 8.4%, 6.4% and 13.4% – test PWC170 , and 12.8%, 14.8% and 21.8 per cent – aerobic performance by GMT. Relative indicators of MSCS girls at the age of 11, 12 and 13 with impaired vision are of the average level of aerobic capacity and girls at the age of 14 – below average.